SPIRITUALITAS KOMUNITAS TRITUNGGAL MAHAKUDUS YOGYAKARTA DALAM PERSPEKTIF TEOLOGI PEMBEBASAN GUSTAVO GUTIERREZ - Natalia Heni Primawati (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
The title of this research is The Spirituality of Komunitas Tritunggal Mahakudus Yogyakarta in the Perspective Gustavo Gutierrez’s Theology of Liberation. Progress of science and technology, globalization climate cause human being to have individualistic and materialism point of views. Social solidarity in modern times began to decrease so that the role religious of community to develop the spiritual life and social life is necessary. Gustavo Gutierrez’s theology of liberation inspires the social solidarity to increase faith in the social praxis and realization. The result of this research: religious community to improve vertical relation and horizontal relation such as Komunitas Tritunggal Mahakudus Yogyakarta. Religious community is not necessary in improving the spiritual aspect but also the real work or caring for the poor. Gustavo Gutierrez’s theology of liberation connects the praxis in commitment, pray, contemplation, action and theology.Gustavo Gutierrez’s theology of liberation inspires the religious communities to act in concrete way for the environment especially the poor.